The Impact of Extrinsic Reward on Learners’ Performance and Motivation in Reading - BILOUK, Imène (Journal of Human Sciences, 2015)
This work examines the impact of extrinsic reward, as a motivation strategy, on students’ L2 reading motivation and performance. A total sample of 91 second year LMD students of English as a foreign language, at the Department of Arts and English Language University of Constantine 1, was involved in reading and performing intensive reading activities for a whole semester. Short stories, as a tangible reward, were offered at the end of each successful reading comprehension performance, to function as reinforcement for enhancing both reading performance and motivation. The results of students’ pre and post-reward reading comprehension performances show that students’ performance in reading was enhanced; whereas, those of the pre and post-reward reading motivation was not.